Прусское deiwas: санскритское devásya, литовское diẽvojis и русское евоный (мифический формант генитива *-si̯o и его отгенитивное склонение - Palmaitis, Letas (Baltistica, 1980)
Sanskrit devásya, Prussian deiwas, Lithuanian diẽvojis, Russian евоный and the mythical genitive formant *-si̯oTo develop the ideas of V. Ivanov and V. Mažiulis, the author states that in course of the decaying of the prenominative IE structure, when the sigmatic nominative/fientive and genitive/fientive forms appeared to be identical, genitive was either differentiated from nominative by stress (so in Prussian and probably in Hittite) or was substituted e. g. by the degenitive adjective form (as in Aryan, Greek and many other languages) of the pattern stem + gen.-s + relative formant (= derivative suffix) *ya (*i̯o) + case endings. The latter is preserved in Anatolian forms of the Luvian maššanaššiš type. Here is the origin of the s. c. “genitive formant” *-si̯o, since genitives of the type Skt. devásya; Horn, λύκοιο etc. are fossilized stems which earlier were declined: nom. *devas-ya-s, acc. *devas-ya-m etc. Prussian ſteſſe, Slavic česo genitives show the archaic vocalization e/o of the sigmatic formant. S. i. devásya, pr. deiwas, lie. diẽvojis, r. евоный ir mitinis genityvo formantas *-si̯oTęsiant V. Ivanovo ir V. Mažiulio mintį, keliama nuomonė, kad ide. priešnominatyvinės sandaros irimo metu sutampant sigmatinėms nominatyvo/fientyvo bei genityvo/fientyvo formoms, genityvas arba tapo diferencijuojamas nuo nominatyvo kirčiu (prūsų kalba, galbūt – hetitų), arba buvo pakeistas, pvz., degenityvine būdvardine forma (arijų, graikų, daugelyje kitų kalbų): kamienas + gen. -s + reliatyvinis formantas (= darybinė priesaga) *ya (*i̯o) + linksnių galūnės. Šis reiškinys išlikęs luv. maššanaššiš tipo anatoliečių formose. Tokios kilmės bus vad. „genityvo formantas“ *-si̯o, nes s. i. devásya, Ноm. λύκοιο tipo genityvai rodo sustabarėjusį kamieną, kadaise linksniuojamą nom. *devas-ya-s, acc. *devas-ya-m tt. Pr. ſteſſe, sl. česo genityvinės formos rodo archainę sigmatinio formanto vokalizaciją e/o.
Keywords: genityvas; indoeuropeistika